Peran Praktik Corporate Social Responbility dalam Memoderasi Hubungan Green Accounting dan Tax Avoidance terhadap Nilai Perusahaan Sektor Energi di BEI Periode 2020 s/d 2024 - Rasmon; Arfah Piliang (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study focuses on the influence of tax avoidance and green accounting on firm value, with Corporate Social Responsibility (CSR) as a moderating factor in energy companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Using a Structural Equation Modeling with Partial Least Squares (SEM-PLS) approach, the study examines the direct relationship and moderating effect between variables based on secondary data from financial reports, CSR reports, and related environmental data. The analysis results indicate that tax avoidance and green accounting have a significant negative effect on firm value. However, CSR serves as a moderating variable that strengthens the positive impact of green accounting on firm value, while the moderating effect of CSR on tax avoidance is insignificant. These findings emphasize the importance of implementing green accounting supported by good CSR practices to sustainably increase the value of energy companies, while also reminding the need to manage tax avoidance practices to avoid reducing market confidence. This study provides an important contribution to managers and regulators in developing sustainability strategies and effective tax management in the energy sector.